E-Business and The Impact of Its Strategy on Job Performance an Applied Study on Islamic Banks - Ali, Alzober Mouftah (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
This study aims to identify the role of e-business strategy and its impact on job performance. The research uses an analytical functional approach and selects a sample of 50 bank customers from Islamic banks in Libya through simple random sampling. The data was processed using appropriate statistical methods, revealing that high-level e-business strategies are positively correlated with improved employee job performance. The study specifically highlights that the infrastructure necessary for e-business, trained personnel, and the effective use of information technology play significant roles in enhancing job performance. The research focuses on Islamic banks in Libya, which have increasingly relied on e-business strategies to offer better services and improve operational performance. The study emphasizes the importance of developing robust electronic systems and ensuring that employees are continuously trained to keep pace with technological advancements. The findings suggest that e-business strategies contribute not only to streamlining processes but also to better data management, increased accuracy, and improved employee satisfaction, leading to enhanced productivity. The study recommends that its findings be disseminated to all banks in Libya, urging the adoption of e-business strategies to enhance job performance. It also suggests further research into the impact of e-business strategies in other sectors and institutions, particularly in developing economies such as Libya. Exploring these strategies across various industries would help build a comprehensive understanding of how they can improve organizational performance. Moreover, this research could contribute to the broader economic development of Libya by encouraging efficient, technology-driven practices in both the public and private sectors.